2017
DOI: 10.1089/aid.2016.0189
|View full text |Cite
|
Sign up to set email alerts
|

Lower Frailty Is Associated with Successful Cognitive Aging Among Older Adults with HIV

Abstract: Aging with HIV poses unique and complex challenges, including avoidance of neurocognitive disorder. Our objective here is to identify the prevalence and predictors of successful cognitive aging (SCA) in a sample of older adults with HIV. One hundred three HIV-infected individuals aged 50 and older were recruited from the Modena HIV Metabolic Clinic in Italy. Participants were treated with combination antiretroviral therapy for at least 1 year and had suppressed plasma HIV viral load. SCA was defined as the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 42 publications
1
23
0
2
Order By: Relevance
“…No consensus currently exists for an operational definition of frailty, and many have suggested that measures of mental health should be included [18]. Our findings support this suggestion, and are consistent with prior studies in HIV demonstrating an association between neuropsychiatric abnormality and frailty status [9,10]. Although the underlying mechanism of this association cannot be determined in our study, prior studies have demonstrated an association between motor abnormality (and with particular relevance to frailty, abnormal gait) and cognitive impairment, both in PLWH and HIV-negative populations [19][20][21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No consensus currently exists for an operational definition of frailty, and many have suggested that measures of mental health should be included [18]. Our findings support this suggestion, and are consistent with prior studies in HIV demonstrating an association between neuropsychiatric abnormality and frailty status [9,10]. Although the underlying mechanism of this association cannot be determined in our study, prior studies have demonstrated an association between motor abnormality (and with particular relevance to frailty, abnormal gait) and cognitive impairment, both in PLWH and HIV-negative populations [19][20][21].…”
Section: Discussionsupporting
confidence: 90%
“…In a functionally intact [i.e. without impairments in activities of daily living (ADL)] subsample from this clinic, cognitive status assessed by three neuropsychologic tests, and depressive symptom index was also correlated with frailty status [9]. In a sample from a tertiary care center in Mexico that excluded severe illnesses, such as COPD and advanced cardiac disease, frailty was related to functional cognitive impairments assessed with the NEUROPSI battery [10].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of significant cognitive decline is an encouraging finding; however, the accrual of motor dysfunction is worrisome. Motor dysfunction is part of many neurologic disorders of aging and has real impact on a person’s ability to age successfully and maintain independence (Wallace et al 2017). The combination of neuropsychological impairment, even if stable and relatively mild, with motor dysfunction may contribute to a frail HIV-infected aging population even in the setting of immune reconstitution and viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…While frailty's impact has provided new insights in prevention and treatment within AD, its effect on cognitive impairment among PLWH has been relatively unexplored. To date, we know that cross-sectionally, among PLWH, low frailty status is associated with the absence of cognitive impairment in older adults (Wallace et al, 2017) and that high frailty is associated with worse global neurocognitive functioning, verbal fluency, executive functioning, processing speed, and motor skills (Oppenheim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%